PENGARUH PENGGUNAAN TEKNOLOGI INFORMASI DALAM PEMBELAJARAN PAI DI SMAIT FAJAR ILAHI - Syafna Amalia Pratiwi; Nur Hariani; Yulian Oktavianti; Atika Salsabila Fajari Ufairah; Muhammad Rohim; Muslimin; Sabrun Jamil (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study investigates the impact of information technology use in Islamic Religious Education (PAI) at SMAIT Fajar Ilahi, addressing challenges in delivering engaging and effective religious learning in the digital era. The rapid advancement of digital tools in education has created both opportunities and barriers for PAI teachers and students to integrate interactive media into learning. The research aims to determine how the use of information technology impacts student engagement, learning outcomes, and instructional delivery in PAI classes. A qualitative case study approach was employed, involving classroom observations, teacher interviews, and documentation of digital learning practices. Data were analyzed thematically to evaluate how technologies such as multimedia, e‑learning platforms, and digital resources influence PAI learning. The findings reveal that information technology enhances interactive learning, expands access to diverse learning resources, and increases student motivation, although challenges in teacher digital readiness and infrastructure remain. Results suggest that when effectively integrated, information technology use contributes positively to the quality of PAI learning by facilitating more dynamic and student‑centered instruction. These insights highlight the importance of strategic planning, teacher training, and pedagogical adaptation in maximizing the benefits of technology in PAI education.